Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1879 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Peromyscus nasutus (J.A.Allen, 1891)", "HasCoordinate is true", "HasGeospatialIssue is false", "Year is greater than or equal to 1950" ] } The dataset includes 1879 records from 18 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0014848-160311141623029/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences